Trouble Free Dopamine Sensing by Palladium Nanoparticles Fabricated Poly(3, 4-ethylenedioxythiophene) Functionalized Graphene. Issue 3 (1st January 2016) - Choe, Ju Eun; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract : An electrochemical sensor based on poly(3, 4-ethylenedioxythiophene) functionalized reduced graphene oxide with palladium nanoparticles (Pd/PEDOT/rGO) has been constructed for electrochemical determination of dopamine (DA) in presence of ascorbic acid (AA) at high concentration. The structural features of the catalyst were characterized using several instrumental methods. The transmission electron microscopy (TEM) analysis suggests a well dispersed spherical PdNPs set successfully onto PEDOT/rGO film. Electrochemical determination of DA in presence of AA was investigated on modified glassy carbon electrode in 0.1 M phosphate buffer solution at pH 7.4 using cyclic voltammetry, differential pulse voltammetry (DPV) and amperometry techniques. A wider linear analytical range for DA detection (1–200 μM) and comparatively lower limit of detection (LOD) 0.14 μM were obtained using DPV technique, while LOD increases up to 0.16 μM in the presence of five times higher AA. Also, no significant interference was observed from similar biomolecule species such as norepinephrine, epinephrine, uric acid and AA. This DA-sensor retained 85.6% of its initial response up to 15 days.